NOD/Scid IL2Rγnull Mice Reconstituted with PBMCs from Patients with Atopic Dermatitis or Psoriasis Vulgaris Reflect the Respective Phenotype - Marietta Schindler; Paula Schuster-Winkelmann; Veronika Weß; Sophia Czell; Franziska Rueff; Andreas Wollenberg; Matthias Siebeck; Roswitha Gropp (JID Innovations, 2024)
NSG (NOD/Scid IL2Rγnull) mice reconstituted with PBMCs donated by patients with ulcerative colitis or Crohn’s disease highly reflect the respective pathological phenotype. To determine whether these findings could be applicable to atopic dermatitis (AD) and psoriasis vulgaris (PV), PBMCs isolated from patients with AD and PV were first subjected to immunological profiling. Subsequently, NSG mice were reconstituted with these PBMCs. Hierarchical clustering and network analysis revealed a distinct profile of patients with AD and PV with activated CD4+ T cells (CD69, CD25) occupying a central position in the AD network and CD4+ CD134+ cells acting as the main hub in the PV network. After dermal application of DMSO, both NSG mice reconstituted with PBMCs from donors with AD (ie, NSG-AD mice) and NSG mice reconstituted with PBMCs from donors with PV (ie, NSG-PV mice) exhibited increased clinical, skin, and histological scores. Immunohistochemical analysis, frequencies of splenic human leukocytes, and cytokine expression levels indicated that CD4+ CD69+ cells, M1 and TSLP receptor–expressing monocytes, switched B cells, and monocyte chemoattractant protein 3 were the driving factors of inflammation in NSG-AD mice. In contrast, inflammation in NSG-PV mice was characterized by an increase in fibroblasts in the epidermis, frequencies of CD1a-expressing monocytes, and IL-17 levels. Therefore, the pathological phenotypes of NSG-AD mice and NSG-PV mice differ and partially reflect the respective human diseases.